PENINGKATAN KOMPETENSI GURU SEKOLAH MENENGAH KEJURUAN DI KABUPATEN SUMBA BARAT DAYA - Ied Veda R Sitepu; Lisa Kailola; Anita Jojor; Mesta Limbong (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
Training activities to improve teacher competence at Don Bosco Vocational School, Southwest Sumba (SBD) involves both Don Bosco teachers as well as external teachers took place on 26-27 August 2022. The objectives of the activity are (1) to share knowledge and experiences; (2) to map the competence of teachers, (3) to plan a knowledge and teaching competence improvement program, and (4) as an initial step to plan teacher competence development in Don Bosco, in particular and in Tambolaka region, in general. The activities cover (1) field observations and (2) teacher FGDs. Teacher competence, ie. pedagogic, social, personal, and professional competencies, must be strengthened and improved. Considering that vocational high school graduates are expected to enter the workforce, the development of teacher human resources is a priority target, however, temporary infrastructure facilities do not need attention because both quantity and quality are adequate. The teacher training that was held was then directed to include teachers around Tambolaka. At the end of the training, the teachers established a communication forum to bridge communication and achieve educational mission together.